Electrical Conductivity in a Porous, Cubic Rare-Earth Catecholate - Skorupskii, Grigorii; Dincă, Mircea (Journal of the American Chemical Society, 2020)
Electrically conductive metal–organic frameworks (MOFs) provide a rare example of porous materials that can efficiently transport electrical current, a combination that is favorable for a variety of technological applications. The vast majority of such MOFs are highly anisotropic in both their structures and properties: Only two electrically conductive MOFs reported to date exhibit cubic structures that enable isotropic charge transport. Here we report a new family of intrinsically porous frameworks made from rare-earth nitrates and hexahydroxytriphenylene. The materials feature a novel hexanuclear secondary building unit and form cubic, porous, and intrinsically conductive structures, with electrical conductivities reaching 10–5 S/cm and surface areas of up to 780 m2/g. By expanding the list of MOFs with isotropic charge transport, these results will help us to improve our understanding of design strategies for porous electronic materials.